Foreign Language Enjoyment and Anxiety as the Correlates of the Ideal L2 Self in the English as a Foreign Language Context - Fathi, Jalil; Mohammaddokht, Farnoosh (Frontiers in Psychology, 2021)
Learners’ emotions in learning a foreign language are claimed to shape complicated dynamic associations contributing to their motivational and linguistic outcomes, as evidenced by recent research in this area. In order to advance this research area, this study sought to investigate the foreign language enjoyment (FLE) and foreign language classroom anxiety (FLCA) as predictors of ideal L2 self in Iranian English as a Foreign Language (EFL) context. The total number of 195 English-major students from various universities completed an online survey containing the three scales in question. The measurement models were first verified using confirmatory factor analysis (CFA). Then the structural model for the relations among the variables was tested employing structural equation modeling (SEM). The SEM results showed that although FLE and FLCA significantly predicted ideal L2 self, FLE was a stronger predictor of ideal L2 self than FLCA. This study provides significant pedagogical implications for EFL practitioners. Keywords: FLCA, FLE, ideal L2 self, EFL, motivation